(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is the science of life and longevity. Its main objective is to maintain the normal health of individuals and secondary is the cure of diseases. For maintaining health it advocates the wholesome diet and proper daily routine. If any disturbance occurs in health condition of individual it then advocates the medicines for cure. The medicines are of herbal, mineral and herbo-mineral in origin. Bhasmas are unique Ayurvedic preparations of metals/minerals formulated with herbal extracts or juices and used for the treatment of a variety of ailments. Bhasma is prepared by incinerating the metals and minerals. For incineration classical and modern methods are used. The Classical Method of Bhasma preparation is Puta and modern method is Electric Muffle Furnace. The herbal juices are used for levigation of powders of metals and minerals. Owing to their micro/ nano fineness, ease of administration and comparatively small dose, they have been known for their wide area of application and therapeutic value. Kasisa is mineral of Iron. It is placed under Uprasa in Rasashastra. Its Bhasma is widely used in different ailments. It is used in the treatment of Agnimandya, Arsha, Kashtartava, Gudabhramsha, Pandu, Shotha, Rajorodha, Yonivyapada. In the present study Kasisa bhasma was prepared as per the reference of Rasamruta and analysed using classical parameters.